Socio-political and administrative determinants of municipal revenue performance: insights from Mozambique - Saida Bunk; Salvador Forquilha; Dominique Klawonn; Jonathan Krull; Alina Sennewald; Conrad Steinhilber; Juliane von Boeselager; Armin von Schiller (Deutsches Institut für Entwicklungspolitik (DIE), 2017)
While in most developing countries revenue potential at the subnational level is modest, there are good reasons for donors and development partners to continue and intensify their efforts in this sector. On the one hand, locally collected revenue, although negligible when compared with revenue collected at the national level, can make a big difference for the fiscal space available to municipalities. On other hand, beyond the availability of more financial resources, stronger local revenue mobilisation is expected to come with a “governance dividend”. As a result, the mobilisation of revenue at the local level is a relevant topic for development, not only from a fiscal point of view, but also from a broader governance perspective. Consequently, stronger revenue mobilisation should not only be seen as an end in itself, but also as a means for promoting good governance. We argue that to unlock these potential positive effects, donors and development partners need a better understanding of the effects that socio-political and administrative determinants have on municipal revenue mobilisation. In this paper, we summarise the insights gained in a study on how administrative and socio-political variables at the local level affect the revenue performance of Mozambican municipalities. Thereby, we contribute to an evolving literature highlighting the relevance of local factors in explaining local revenue mobilisation. Results show that, first, administrative weaknesses lead to strong reliance on certain easy-to-implement revenue instruments that are not necessarily those with the highest revenue potential. Moreover, the results highlight the systemic nature of the process of revenue collection: failure or lack of capacity concerning one single step strongly affects the effectiveness and efficiency of the whole revenue collection system. Second, municipal governments that are politically aligned with the party governing at the national level show fewer efforts to increase revenue performance than non-aligned governments. This shows how political variables at the local level, especially in the interaction with other levels of government can strongly affect the incentives for municipalities to exploit their revenue potential. Third, in the context of a generally weak civil society, marginal variations in organisational strength do not seem to affect the fiscal behaviour of local governments. In this line, we find that the civil society at the local level in Mozambique lacks the capabilities to shape and influence revenue mobilisation in any meaningful way, even where they have donors' support. These results have strong implications for donors and development partners. Not considering the effects of socio-political and administrative factors on revenue performance strongly limits the capacity of donors to anticipate the prospective effectiveness of policies and measures aimed at increasing local revenue mobilisation. In this line, practitioners need to broaden their approach to municipal revenue mobilisation and more systematically consider how socio-political and administrative variables shape prospects for stronger impacts to be achieved.
Keywords: 330; Entwicklungsfinanzierung und öffentliche Finanzen; Governance